2014
DOI: 10.1007/s11010-014-2232-y
|View full text |Cite
|
Sign up to set email alerts
|

Melanin Nanoparticles (MNPs) provide protection against whole-body ɣ-irradiation in mice via restoration of hematopoietic tissues

Abstract: During radiotherapy, ionizing irradiation interacts with biological systems to produce free radicals, which attack various cellular components. The hematopoietic system is easily recognized to be radiosensitive and its damage may be severe. Melanin nanoparticles (MNPs) act as free radical scavengers prepared by polymerization of dopamine. In this study, a total of 110 male BALB/C mice were divided into five equal groups. Each group contained 22 mice. Mice of group A did not receive MNPs or irradiation (control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
31
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 38 publications
1
31
0
Order By: Relevance
“…Thus, our group further developed nano-droplets of PFC stabilized by albumin as an oxygen shuttle for tumor-specific delivery of oxygen with the help of tumor-focused low-intensity ultrasound (Figure 13). 2017, 29,1700996 Hemoglobin-based oxygen carrier [230,237] Perfluorocarbon (PFC) emulsions; BSA coated PFC emulsion; PFC loaded hollow Bi 2 Se 3 ; TaOx decorated with PFC nanodroplets [238][239][240][241] Mild hyperthermia [39,71,73] Increase tumor oxygenation by catalysis of endogenic H 2 O 2 MnO 2 nanopartilces; MnO 2 nanosheets@ upconversion; Au@MnO 2 core-shell [242][243][244][245][246][247] Polymer micelles encapsulating catalase and TaOx@catalase [248][249][250] Hypoxia-specific therapy accompany hypoxia-specific cytotoxicity of tirapazamine [58,251] X-ray controlled NO releasing [56] Radioprotection to reduce side effects Free radical scavengers CeO 2 nanoparticles [252,253] Melanin nanoparticles [254,255] MoS 2 dots [256] Oxygen-loaded nanoparticles were able to enhance tumor oxygenation triggered by the NIR laser. injected into tumorbearing mice under hyperoxic breathing.…”
Section: Increase Of Tumor Oxygenation By Oxygen Deliverymentioning
confidence: 99%
“…Thus, our group further developed nano-droplets of PFC stabilized by albumin as an oxygen shuttle for tumor-specific delivery of oxygen with the help of tumor-focused low-intensity ultrasound (Figure 13). 2017, 29,1700996 Hemoglobin-based oxygen carrier [230,237] Perfluorocarbon (PFC) emulsions; BSA coated PFC emulsion; PFC loaded hollow Bi 2 Se 3 ; TaOx decorated with PFC nanodroplets [238][239][240][241] Mild hyperthermia [39,71,73] Increase tumor oxygenation by catalysis of endogenic H 2 O 2 MnO 2 nanopartilces; MnO 2 nanosheets@ upconversion; Au@MnO 2 core-shell [242][243][244][245][246][247] Polymer micelles encapsulating catalase and TaOx@catalase [248][249][250] Hypoxia-specific therapy accompany hypoxia-specific cytotoxicity of tirapazamine [58,251] X-ray controlled NO releasing [56] Radioprotection to reduce side effects Free radical scavengers CeO 2 nanoparticles [252,253] Melanin nanoparticles [254,255] MoS 2 dots [256] Oxygen-loaded nanoparticles were able to enhance tumor oxygenation triggered by the NIR laser. injected into tumorbearing mice under hyperoxic breathing.…”
Section: Increase Of Tumor Oxygenation By Oxygen Deliverymentioning
confidence: 99%
“…The radioprotective properties of melanins are of high interest for a number of different potential applications, including the development of novel and effective radioprotective materials for saving cancer patients undergoing radiation therapy from the side‐effects of ionizing radiation treatment, and protection of astronauts from space radiation in manned space missions. Data confirm that radioprotective properties of fungal melanins can be exploited in mammalian systems; in fact, it was recently reported that internal administration of melanin protected mice against experimental lethal irradiation (Schweitzer et al ., ; Kunwar et al ., ; Revskaya et al ., ; Rageh et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…[18] We therefore explored the γ-irradiation protection function of MMNs on healthy female BALB/c mice. Mice were challenged with a lethal dose of γ-irradiation using 60 Co source.…”
mentioning
confidence: 99%
“…Other than physical shielding and quenching of cytotoxic-free radicals, [20] melanin also showed abilities in modulation of pro-survival pathways, prevention of oxidative stress and potent immunomodulation. [18, 21] Therefore, MMNs might be useful and serve as a potential radioprotector to shield the normal organs of cancer patients who are undergoing high dose radiotherapy.…”
mentioning
confidence: 99%